1997
DOI: 10.1111/j.1439-0434.1997.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Les Phénolamides des Rachis de Palmes, Composants de la Réaction de Défense du Palmier Dattier vis‐à‐vis de Fusarium oxysporum f.sp. albedinis, Agent Causal du Bayoud

Abstract: Phenolamides in the Rachis of Palms: Components of the Defence Reaction of the Date‐palm towards Fusarium oxysporum f.sp. albedinis, the Causal agent of ‘Bayoud’ This is the first study showing evidence of the production of phenolic and phenolamidic compounds in date palm tissues in response to attack by Fusarium oxysporum f.sp. albedinis (Foa), the causal agent of the wilt called bayoud. Marked quantitative and qualitative differences were recorded in the production of such compounds when infected and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…PAs are likely to play multiple defence roles in plants (reviewed in Bassard et al 2010). For example, PAs accumulated in response to virus infections in tobacco plants (Martintanguy et al 1976;Torrigiani et al 1997;Rabiti et al 1998), and PAs showed antimicrobial properties in several other plant-pathogen interactions (Grandmaison et al 1993;Ramos et al 1997;Von Röpenack et al 1998;Campos et al 2014). With regard to virus transmission by sucking insects, BPH-induced CoP and FP accumulations ( Fig.…”
Section: Defence Functions Of Pasmentioning
confidence: 99%
“…PAs are likely to play multiple defence roles in plants (reviewed in Bassard et al 2010). For example, PAs accumulated in response to virus infections in tobacco plants (Martintanguy et al 1976;Torrigiani et al 1997;Rabiti et al 1998), and PAs showed antimicrobial properties in several other plant-pathogen interactions (Grandmaison et al 1993;Ramos et al 1997;Von Röpenack et al 1998;Campos et al 2014). With regard to virus transmission by sucking insects, BPH-induced CoP and FP accumulations ( Fig.…”
Section: Defence Functions Of Pasmentioning
confidence: 99%
“…The main disease control method currently available is the multiplication and use of tolerant/resistant cultivars. Such tolerance/resistance has been reported to be due to the activation of peroxidases (Baaziz, 1989), glucanases and chitinases (Amraoui, 1993), as well as to the accumulation of phenolics (Ziouti et al, 1996; El Hadrami et al, 1997), among which a crucial role has been attributed to hydroxycinnamic acid derivatives (El Hadrami et al, 1997; Ramos et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylamides are secondary metabolites that result from the conjugation of aliphatic polyamines or arylmonoamines and hydroxycinnamic acids (Walters 2003;Edreva et al 2007). These secondary metabolites have been reported in many plant responses to biotic and abiotic stresses (Martin-Tanguy et al 1973;Clarke 1982;Ramos et al 1997). For instance, formation of highly fluorescent conjugates of cinnamic and p-coumaric acids, with either tyramine or octopamine, were often observed in potato tuber tissues inoculated with an avirulent isolate of Phytophthora infestans (Clarke 1982).…”
Section: Discussionmentioning
confidence: 99%